Effects of modified atmosphere packaging and carcass chill rate on pork loins - Sorheim, O.; Hunt, Melvin C.; Menninen, M.; Warren, K.E.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Use of 10% oxygen in a modified gas atmosphere package resulted in more off-odor, higher microbial counts, and a less desirably colored loin and loin chops. Furthermore, it reduced chop display life and is not recommended.
Keywords: Swine; Pork; Shelf life; Packaging; Quality; Oxygen